Low expression of SOD and PRX4 as indicators of poor prognosis and systemic inflammation in colorectal cancer - An, Sanghyun; Kwon, Hye Youn; Kim, Kwangmin; Kim, Soo-Ki; Kim, Cheol Su; Kim, Bora; Do, Hyejin; Kim, Youngwan (Frontiers in Oncology, 2025)
ObjectivesOxidative stress, characterized by an imbalance between the levels of reactive oxygen species (ROS) and antioxidants, plays a critical role in cancer progression. However, the prognostic significance of antioxidant markers in colorectal cancer (CRC) remains unclear. This study aimed to evaluate the expression of antioxidant markers in tumor tissues and investigate their association with clinicopathological features, survival, and systemic inflammation.MethodsWe retrospectively analyzed 70 patients with CRC who underwent curative surgical resection. The tissue levels of superoxide dismutase (SOD), glutathione peroxidase (GPx), peroxiredoxin 4 (PRX4), and thioredoxin (Trx) were measured in freshly frozen tissues, and the patients were classified into high and low expression groups using the 1st quartile as the cutoff. Associations between antioxidant levels in tumor tissue using ELISA and clinicopathological characteristics, laboratory inflammatory markers, and survival outcomes were analyzed.ResultsLow SOD expression was significantly associated with a higher incidence of distant metastases. Similarly, low PRX4 expression was correlated with more aggressive tumor characteristics, including higher rates of distant metastasis, poor differentiation, and advanced T4 stage. Moreover, low PRX4 levels were linked to systemic inflammation, as reflected by increased neutrophil counts and neutrophil-lymphocyte ratio. Although not statistically significant, the low SOD and PRX4 groups exhibited worse 5-year disease-free survival.ConclusionsLow SOD and PRX4 expression was associated with aggressive tumor features, poor survival, and heightened systemic inflammation in patients with CRC. Given their association with tumor aggressiveness and systemic inflammation, antioxidant markers such as SOD and PRX4 may serve as supportive prognostic biomarkers to help identify patients at risk of adverse clinical outcomes in CRC.